Seize the time - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen portrait of Bobby Seale who was the co-founder of the Black Panther Party in Oakland, California. Caption of the poster is "SEIZE THE TIME" which is part of the title of his book; "Seize the Time: The Story of the Black Panther Party and Huey P. Newton", published in 1970.